Enrollment in Ethiopia's Community-Based Health Insurance Scheme. (October 2015) - Mebratie, Anagaw D.; Sparrow, Robert; Yilma, Zelalem; Alemu, Getnet; Bedi, Arjun S.
Highlights: CBHI enrollment in Ethiopia is analyzed using household and health facility data. In less than two years scheme uptake reached 45.5% of target households. CBHI uptake is pro-poor and influenced by quality of care but not by adverse selection. Almost all the insured intend to renew, a majority of the uninsured plan to enroll. Linking CBHI to existing social programs and government structures boosts uptake. Summary: In June 2011, the Ethiopian government launched a Community-Based Health Insurance scheme. By December 2012, enrollment reached 45.5%. This paper examines uptake. Socioeconomic status does not inhibit uptake and food-insecure households are more likely to enroll. Chronic diseases and self-assessed health status do not induce enrollment, while past expenditure does. A relative novelty is the identification of quality of care. Both the availability of equipment and waiting time to see medical professionals substantially influences enrollment. Focus-groups raise concerns about providers favoring uninsured households. Nevertheless, almost all insured households want to renew and majority of uninsured want to enroll.